FOOD CONSUMPTION ACCORDING TO PYRAMID PROPOSED FOR PATIENTS UNDERGOING BARIATRIC SURGERY - Fabiana Melo Soares; Epifânio Feitosa da Silva Neto; Caroline Trindade da Silva; Thamires Fernanda Silva Vasconcelos; Oscar Felipe Falcão Raposo; Márcia Ferreira Cândido de Souza; Kiriaque Barra Ferreira Barbosa (Universidade do Estado do Rio de Janeiro, 2013)
This study aimed to evaluate the adequacy of food consumption frequency according to food pyramid proposed for postoperative patients of bariatric surgery. It is a cross-sectional study, non-random sampling by convenience, and assessing 39 patients of both genders, aged among 40-59 years, who underwent bariatric surgery and were assisted by the Brazilian National Health System (SUS) at an outpatient clinic of the University Hospital of Sergipe. We selected to participate in the study patients who have been at least two months in post-bariatric surgery follow-up. The study compared the food portions consumed by patients, based on an average of at least two 24-hour dietary recalls on consecutive visits, as recommended by the food pyramid proposed for patients after bariatric surgery. The postoperative nutritional status of patients was distributed from eutrophy to obesity grade III. The average time of preoperative care was 38.89 months. There was inadequacy of consumption in level 1 (Group of meat, eggs, dairy products, and legumes); level 2 (Group of vegetables and olive oil) and foods with high contents of fat and sugar; and adequacy at level 2 (fruits group) and level 3 (cereals, roots and tubers). Changing eating habits is a continuous process and does not refer only to the surgical procedure. Thus, the construction of knowledge on the dietary pattern of the population in the long term is paramount for guidance and prevention of nutritional deficiencies.